Evaluating a social marketing campaign on healthy nutrition and lifestyle among primary-school children: A mixed-method research design. (December 2021) - Nosi, Costanza; D'Agostino, Antonella; Pratesi, Carlo Alberto; Barbarossa, Camilla
Highlights: A mixed-method research is used to evaluate a social marketing campaign (SMC) on healthy nutrition and lifestyle of children. SMCs are effective in increasing children's nutrition-related knowledge, improving their eating habits and reducing their sedentary behavior. Increasing children's acceptance of healthful nourishment can represent a valuable means for improving the dietary habits of their entire family. Mixed-method research designs are effective tools for evaluating societal interventions such as those aimed at educating children. Abstract: Italy has one of the highest levels of childhood overweight and obesity in Europe. Therefore, preventing children from becoming overweight is a major public health challenge. Here, we used a mixed-method research approach – including a quasi-experimental design and three surveys – to create a formative evaluation of a social marketing campaign on healthy nutrition and lifestyle in Italian primary school children. The social marketing campaign was organized around the 4 Ps of the marketing mix ( product : the educational activities; place : the involved schools and supermarkets; promotion : the in-person and technology-based communication; and price : hours spent by the targeted children in fulfilling the educational activities). The campaign involved primary-school children across four Italian cities. The findings suggest that social marketing education campaigns can be effective tools to improve children's knowledge about healthy food and lifestyle, reduce their sedentary behavior, and increase their consumption of healthy food. Also, increasing children's acceptance of healthful nourishment is a valuable tool to improve the dietary habits of the entire family. With relation to the educational program assessment method, this study can inform societal interventions especially those involving children through the integration of different qualitative and quantitative research methods, which collect data from different subjects and perspectives.